Berbamine dihydrochloride suppresses the progression of colorectal cancer via RTKs/Akt axis. (1st March 2023) - Liu, Lu; Liang, Dan; Zheng, Qiao; Zhao, Maoyuan; Lv, RuiTing; Tang, Jianyuan; Chen, Nianzhi
Abstract: Ethnopharmacological relevance: Berberis amurensis Rupr. is used to treat cancer as a traditional herbal medicine. Berbamine (BBM) is a natural bisbenzylisoquinoline alkaloid extracted from Berberis amurensis which possesses multiple pharmacological activity including anticancer. Aim of the study: To investigate the influence of BBM on the progression of colorectal cancer (CRC) and further explore the underlying mechanism of BBM based on the RTKs/Akt signaling pathway. Materials and methods: In vitro, cell viability and colony formation were conducted to detect BBM inhibitory of CRC cell lines. Transwell was detected the ability of migration and invasion by BBM. Apoptosis detection assay, cell cycle assay and the measurement of ROS were detected to confirm the inductive effect of cell apoptosis. RT-qPCR and Western blot to clarify the specific mechanism of anticancer. Finally, we conducted HE staining, Ki67, Tunnel and immunochemistry were confirmed the anti-colorectal cancer activity of BBM from vivo study. Results: We found that BBM could inhibit CRC cell lines growth. Moreover, BBM presented an inhibitory effect the ability of migration and invasion in CRC cells. Furthermore, the occurrence of apoptosis was involved in the anti-colorectal cancer role of BBM. BBM also triggered ROS accumulation in CRC cells that might be a key factor for the inductive effect of BBM in cell apoptosis. Cell cycle assay revealed that BBM induced the arrest of G1-S phase and increased the p21 levels but decreased CyclinE1, CyclinE2, CDK6, CyclinD1. RT-qPCR manifested that the down-regulation effect of BBM on AKT1, EGFR, PDGFRα and FGFR4 genes. The results also showed that BBM could decreased the expression levels of phosphor-AKT, PDGFRα, PDGFRβ, EGFR, FGFR3 and FGFR4 which belong to RTKs family. Consistently, BBM remarkably suppressed tumor xenograft growth in nude mice. Conclusion: Taken together, all the results as presented above suggest that BBM as a novel multitargeted receptor tyrosine kinase inhibitor plays a crucial role in the inhibitory effect of CRC and may be a promising therapeutic agent for the CRC in clinic. Graphical abstract: Image 1 Highlights: BBM exerts strong anti-colorectal cancer effect both in vitro and in vivo. BBM inhibits the progression of colorectal cancer through inducing apoptosis, suppressing proliferation, migration, invasion of cells. BBM is a novel multitargeted receptor tyrosine kinase (RTK) inhibitor from natural products. RTKs/Akt signaling pathway plays a vital role in the anti-colorectal cancer effect of BBM.